Supporting Stressed Students: How Veteran Educators Recognize and Address Academic Stress - Lisa Konieczna; Gail Collins (SAGE Open)
Academic stress is a worldwide issue that impacts adolescent students and their educators. While educators may assist students in managing academic stress, they must first recognize students’ feelings of academic stress. Consequently, both recognizing and addressing academic stress were considered in this study. The theoretical framework consisted of a combination of Lazarus and Folkman’s transactional model of stress to frame students’ experiences of academic stress, and Dweck’s theory of mindset to consider educators’ perspectives about students’ growth. Participants included 10 veteran educators, selected through purposeful sampling. A hermeneutical phenomenological qualitative design was applied. Data collection methods included interviews, focus groups, and letters of advice. Analysis through phenomenological reduction revealed that educators recognized academic stress through observations of students’ behaviors and body language. Educators intervened to support students experiencing academic stress with coping strategies, mindset strategies, and strategies they had developed over their careers. The results of this study include a collection of strategies veteran educators apply to recognize and address academic stress in adolescent students.